Implementasi Sistem Pendeteksi Ketinggian Air Dengan Menggunakan Wireless Sensor Network Node Point To Point - Moch Rizki Cahyadi; Sabriansyah Rizqika Akbar; Edita Rosana Widasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Siltation caused by erosion of soil in river is also a constriction caused by existence of illegal buildings built in watershed. This condition causes water capacity of river smaller, causing river overflow and flooding occurs. Use ultrasonic sensors as water level detection can done to determine increase water level in river. Sending one data to one computer becomes ineffective because the number of devices required. Point-to-point routing method can be a solution to solve problem. Through this method, user doesn't need to monitor one data from one node. River height data will sent by nodes to gateway so that only requires one device connected to computer. This research implements point-to-point routing as communication method of river water level detection system using nRF24L01 communication module. The system designed to transmit obtained data by node to gateway. Gateway will receive data from node, then program will created display in graphical form. From the results of tests conducted level of accuracy of ultrasonic sensors more than 89%. The data reading on the prototype has an accuracy 80%. Data delivery has 100% accuracy. System functional test results can display graphs that indicate functionality of mqtt and websocket features on system.